El Concilio Vaticano II y el ethos revolucionario en la Argentina de los sesenta-setenta - Pablo Ponza (Nuevo mundo - Mundos Nuevos, 2008)
The main idea in this article is to analyze some of the political and religious effects that the theological, liturgical and pastoral renewal process of the Second Vatican Council (1962-1965) had over the Catholic Argentinian community. Such a process exerted an important ideological influence in the development of some rebellious political organizations during the sixties- seventies period (1959-1973). This was the case, for instance, of the Priest Movement for the Third World (MSTM) or the political and military organization of the Montoneros. They constitute two modes of expression that, in a different way and in a different degree, articulated the post-conciliar discourse together with the revolutionary and liberationist, non-confessional one that prevailed in the Third World, especially in Latin America, since the triumphant Cuban Revolution.